Elektronik Dalam Pembuktian Unsur Mens Rea Pada Tindak Pidana Korupsi: Studi Kasus Penyalahgunaan Wewenang - Farah Faricasari Firjatullah Faqih; Mimin Mintarsih (Veteran Law Review, 2026)
The development of information technology has given rise to new forms of electronic evidence that are crucial in the enforcement of criminal law. In the context of corruption, various cases show that digital evidence such as emails, instant messages, recorded conversations, or banking transactions often becomes the key to uncovering the modus operandi and criminal patterns. This study aims to examine the position of electronic evidence in the evidentiary system of corruption crimes in Indonesia and evaluate its role in proving the mens rea (criminal intent) element in corruption cases involving abuse of authority. The research method used is normative legal research with a literature review approach. The results indicate that electronic evidence is normatively recognized as valid within the evidentiary system in Indonesia and plays a significant role in proving mens rea in cases of abuse of authority. Digital information helps strengthen allegations of intent by showing plans or hidden motives in corruption acts. Therefore, clear regulations and improved capacity of law enforcement officials are essential so that electronic evidence can be optimally utilized without disregarding the principles of a fair trial.